Genome-wide DNA methylation profiling by modified reduced representation bisulfite sequencing in Brassica rapa suggests that epigenetic modifications play a key role in polyploid genome evolution - Chen, Xun; Ge, Xianhong; Wang, Jing; Tan, Chen; King, Graham J.; Liu, Kede (Frontiers in Plant Science, 2015)
Brassica rapa includes some of the most important vegetables worldwide as well as oilseed crops. The complete annotated genome sequence confirmed its paleohexaploid origins and provides opportunities for exploring the detailed process of polyploid genome evolution. We generated a genome-wide DNA methylation profile for B. rapa using a modified reduced representation bisulfite sequencing (RRBS) method. This sampling represented 2.24% of all CG loci (2.5 x 105), 2.16% CHG (2.7 x 105) and 1.68% CHH loci (1.05 x 105) (where H = A, T or C). Our sampling of DNA methylation in B. rapa indicated that 52.4% of CG sites were present as 5mCG, with 31.8% of CHG and 8.3% of CHH. It was found that genic regions of single copy genes had significantly higher methylation compared to those of two or three copy genes. Differences in degree of genic DNA methylation were observed in a hierarchical relationship corresponding to the relative age of the three ancestral subgenomes, primarily accounted by single-copy genes. RNA-seq analysis revealed that overall the level of transcription was negatively correlated with mean gene methylation content and depended on copy number or associated with the different subgenomes. These results provide new insights into the role epigenetic variation plays in polyploid genome evolution, and suggest an alternative mechanism for duplicate gene loss.